问题 解答题
计算.
4
5
+
11
15
+
3
10
6-(
3
4
-
3
5
4
3
-(
2
5
+
3
10
5
9
+(
3
4
-
1
2
2
3
+
7
10
+
1
3
+
3
10
1-(
1
6
-
1
7
)+
1
6
答案

(1)

4
5
+
11
15
+
3
10

=

48
60
+
44
60
+
18
60

=

11
6

(2)6-(

3
4
-
3
5

=6-

3
20

=5

17
20

(3)

4
3
-(
2
5
+
3
10

=

4
3
-
7
10

=

40
30
-
21
30

=

19
30

(4)

5
9
+(
3
4
-
1
2

=

5
9
+
1
4

=

20
36
+
9
36

=

29
30

(5)

2
3
+
7
10
+
1
3
+
3
10

=(

2
3
+
1
3
)+(
7
10
+
3
10

=1+1

=2;

(6)1-(

1
6
-
1
7
)+
1
6

=1-

1
6
+
1
7
+
1
6

=(1+

1
7
)+(
1
6
-
1
6

=1

1
7
+0

=1

1
7

选择题
单项选择题 A1型题